Age-Related Differences in the Gut Microbiome of Rhesus Macaques. (13th February 2020) - Adriansjach, Julie; Baum, Scott T; Lefkowitz, Elliot J; Van Der Pol, William J; Buford, Thomas W; Colman, Ricki J
Abstract: Aging is a multifactorial process characterized by progressive changes in gut physiology and the intestinal mucosal immune system. These changes, along with alterations in lifestyle, diet, nutrition, inflammation and immune function alter both composition and stability of the gut microbiota. Given the impact of environmental influences on the gut microbiota, animal models are particularly useful in this field. To understand the relationship between the gut microbiota and aging in nonhuman primates, we collected fecal samples from 20 male and 20 female rhesus macaques ( Macaca mulatta ), across the natural macaque age range, for 16S rRNA gene analyses. Operational taxonomic units were then grouped together to summarize taxon abundance at different hierarchical levels of classification and alpha- and beta-diversity were calculated. There were no age or sex differences in alpha diversity. At the phylum level, relative abundance of Proteobacteria and Firmicutes and Firmicutes to Bacteriodetes ratio were different between age groups though significance disappeared after correction for multiple comparisons. At the class level, relative abundance of Firmicutes_Bacilli decreased and Proteobacteria_Alphaproteobacteria and Proteobacteria_Betaproteobacteria increased with each successively older group. Only differences in Firmicutes_Bacilli remained significant after correction for multiple comparisons. No sex differences were identified in relative abundances after correction for multiple comparisons. Our results are not surprising given the known impact of environmental factors on the gut microbiota.